ANALISIS KINERJA KEUANGAN PADA KANTOR PDAM KABUPATEN SINJAI - Ibrahim H. Ahmad (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
The research is aimed at analyzing the financial performance of PDAM of Sinjai Regency. Some aspects studied in the research are performances of financial, operational and administration. Quantitative approach will be used because it is descriptive and normative. Descriptive means that the approach will give description with understanding about the company’s condition while normative means that it will be accorded to the ideal guidance and norms where they refer to the standards, the legal basis and limitation issued by an institution. The research takes Kepmendagri No. 47/1999 as the guidance. Qualitative approach is a method of collecting data by using list of questions or statements. The research use random proportional in taking the samples for the customer’s instrument in the customer service of PDAM of Sinjai Regency. There are 120 samples with the number of the company’s instrument to the employees are 30 samples. The result shows that the financial performance in the financial aspect is illiquid and insolvable because PDAM of Sinjai Regency faces a financial distress. In operational aspect, based on the level of customer satisfaction, most of the customers are not satisfied of the company’s service because of water continuity and bad service facility. In administration aspect, of ten indicators, most of them are categorized as good. The aspects portrays that the success rate of PDAM of Sinjai Regency is not good in year of 2017.